2022
DOI: 10.3390/healthcare10020238
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Quality of Studies Developing and Validating Melanoma Prediction Models: An Assessment Based on the TRIPOD Statement

Abstract: Transparent and accurate reporting is essential to evaluate the validity and applicability of risk prediction models. Our aim was to evaluate the reporting quality of studies developing and validating risk prediction models for melanoma according to the TRIPOD (Transparent Reporting of a multivariate prediction model for Individual Prognosis Or Diagnosis) checklist. We included studies that were identified by a recent systematic review and updated the literature search to ensure that our TRIPOD rating included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Embracing reporting guidelines such as TRIPOD, can enhance future research reporting standards. 52 Second, none of the studies reported a decision curve analysis to assess the clinical implications of the models. Third, comparing the included models was problematic and meta-analysis was not feasible due to the variety in the predictors and statistical measures used for model performances.…”
Section: Discussionmentioning
confidence: 99%
“…Embracing reporting guidelines such as TRIPOD, can enhance future research reporting standards. 52 Second, none of the studies reported a decision curve analysis to assess the clinical implications of the models. Third, comparing the included models was problematic and meta-analysis was not feasible due to the variety in the predictors and statistical measures used for model performances.…”
Section: Discussionmentioning
confidence: 99%
“…An important additional contribution to the positive development is made by the large number of checklists and accompanying guidance papers that have been published in recent years. These include reporting guidelines such as TRIPOD (Transparent Reporting of a multivariate prediction model for Individual Prognosis Or Diagnosis) [ 81 ], which provides a checklist of 22 items essential for transparent reporting of a prediction model study [ 15 ]. It ensures that all relevant key details on the development process and model performance, which are needed to objectively appraise the validity and usefulness of the model, are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Details on the study selection and eligibility criteria were published previously in a report describing the reporting quality of melanoma prediction studies [ 15 ]. In brief, we included studies reporting the development and validation of models for predicting the individual risk of occurrence of cutaneous melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…GLs are a ubiquitous communication tool (Kaiser et al 2022 ; Valentine 2017 ), often constituted of expert consensus reports of best practise (Shaneyfelt and Centor 2009 ). They aim to provide standardised, evidence-based advice by which decision-makers can determine the course and nature of action (Shen et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%